Marantic Endocarditis Associated with COVID-19: A Rare Case Report of a Potentially Deadly Disease - Chan, Kok Hoe (Eur J Case Rep Intern Med, 2021)
Coronavirus disease 2019 (COVID-19) has overwhelmed healthcare globally with millions of cases and over 2 million deaths worldwide. The hypercoagulable state associated with COVID-19 is a well-recognized complication that carries a poor prognosis. Marantic endocarditis, or non-bacterial thrombotic endocarditis (NBTE), is caused by a sterile vegetation on the cardiac valves resulting from the deposition of fibrin and platelet aggregates. It is highly associated with the hypercoagulable and acquired inflammatory states. Herein, we report a unique and rare case of COVID-19 presenting with NBTE. LEARNING POINTS: COVID-19 has caused a major global pandemic, with high morbidity and mortality. One of the complications of COVID-19 infection is a hypercoagulable state. To the best of our knowledge, we present only the second case of marantic endocarditis in a patient with COVID-19, in the hope of raising awareness among physicians of this potential rare association.